Environmental and socioeconomic factors of abandonment of rainfed and irrigated crops in northeast Spain. (January 2018) - Vidal-Macua, Juan José; Ninyerola, Miquel; Zabala, Alaitz; Domingo-Marimon, Cristina; Gonzalez-Guerrero, Oscar; Pons, Xavier
Abstract: Changes over the last century in the economic model of European countries and the development of the market economy have led to intense shifts in land occupation patterns. Agricultural abandonment is an important consequence of these processes and has modified natural and cultural landscapes, involving side-effects for society. Understanding how environmental and socio-economic factors influence the abandonment process can provide useful insights for managing investments, whether from the public or the private sector. In Spain, the Pyrenees and the Ebro Depression are two differentiated areas in terms of land-use dynamics, particularly in terms of the agricultural model carried out. In this paper we have analyzed the agricultural abandonment in these areas during the 1987–2012 period in relation to several potential explanatory factors. The analysis focuses on the abandonment of rainfed and irrigated herbaceous crops in order to derive specific explanations according to the crop type and geographical region. Crop covers were classified from four Landsat scenes, and conditions were described by topographic variables, human factors and drought occurrence. Boosted regression trees (BRT) were used to identify the most important variables and to describe the relationships between agricultural abandonment and key factors. Topography derived variables were found to be the main determinants, except for irrigated crops in the Ebro Basin, where locational factors play a more important role. BRT models allowed us to identify other significant patterns such as: the vulnerability of irrigated crops to drought; the higher dependence of agricultural activity in the Pyrenees on internal networks; pattern shifts of land abandonment in the analyzed sub-periods, and; evidence of the importance of economic diversification for maintaining cropland. Highlights: Environmental constraints are the main factors affecting abandonment. Irrigated crops in the Central Ebro Basin are more dependent on locational factors. Irrigated herbaceous crops are more prone to being abandoned when droughts occur. Agriculture in the Pyrenees is more dependent on internal markets. Economic diversification could contribute to maintaining cropland.